Evaluation of the SD bioline cholera rapid diagnostic test during the 2016 cholera outbreak in Lusaka, Zambia. Issue 8 (29th June 2018) - Mwaba, John; Ferreras, Eva; Chizema‐Kawesa, Elizabeth; Mwimbe, Daniel; Tafirenyika, Francis; Rauzier, Jean; Blake, Alexandre; Rakesh, Ankur; Poncin, Marc; Stoitsova, Savina; Kwenda, Geoffrey; Azman, Andrew S.; et al.
Abstract: Objective: To assess the performance of the SD Bioline Cholera Ag O1/O139 rapid diagnostic test (RDT) compared to a reference standard combining culture and PCR for the diagnosis of cholera cases during an outbreak. Methods: RDT and bacterial culture were performed on site using fresh stools collected from cholera suspected cases, and from stools enriched in alkaline peptone water. Dried stool samples on filter paper were tested for V. cholerae by PCR in Lusaka (as part of a laboratory technology transfer project) and at a reference laboratory in Paris, France. A sample was considered positive for cholera by the reference standard if any of the culture or PCR tests was positive for V. cholerae O1 or O139. Results: Among the 170 samples tested with SD Bioline and compared to the reference standard, the RDT showed a sensitivity of 90.9% (95% CI: 81.3–96.6) and specificity of 95.2% (95% CI: 89.1–98.4). After enrichment, the sensitivity was 95.5% (95% CI: 87.3–99.1) and specificity 100% (95% CI: 96.5–100). Conclusion: The observed sensitivity and specificity were within recommendations set by the Global Task Force for Cholera Control on the use of cholera RDT (sensitivity = 90%; specificity = 85%). Although the sample size was small, our findings suggest that the SD Bioline RDT could be used in the field to rapidly alert public health officials to the likely presence of cholera cases when an outbreak is suspected.